Exploration of Some Important Fodder Plants of Joshimath area of Chamoli District of Garhwal, Uttarakhand - Nautiyal, Meena*; Tiwari, Jay Krishn; Rawat, Dinesh Singh (Current Botany, 2017)
India has more than 13% of the total livestock population of the world, but it does not have specially identified and regularly managed pastures.Though about 12 million hectares of the land in the country is officially recorded as the grazing land, a vast majority of the population depends on forest for fodder. Livestock is considered as one of the main sources of livelihood, which depends mostly on fodder. Fodder is extracted from forests, grasslands, agricultural land and agro forestry practices. Agriculture with animal husbandry is the main profession of rural people of this Himalayan region. Livestock plays an important role in the economy of Uttarakhand as it is the important source of income of rural people. There is a vast diversity of fodder plants. Demand for fodder is uniform throughout the year, though unavailability of green forage during winter has always remained a serious issue resulting into nutritional deficiency in milching animals. Thus, there is a need to explore fodder plants in Garhwal Himalaya. The present study was conducted to find out the diversity of fodder plants and their seasonal availability and mode of use in Chamoli district. The study covers some villages of Joshimath area of Chamoli district of Garhwal which lie in between 30º26´52.37 ̋̋ to 30º33´02.52 ̋ N Latitude and 79º33´57.56 ̋ to 79º41´34.79 ̋ E Longitude. The survey was conducted in the years 2014 and 2015. Information on locality, mode of use and seasonal availability was recorded by interviewing the people of the studied villages. The findings recorded 89 fodder species representing trees, shrubs, herbs, grasses and climbers. During the rainy season the availability of fodder is in plenty, but there is fodder crisis in other seasons of the year as people are not aware of scientific conservation of grasses for lean periods. It was observed that more fodder species are needed to be planted to increase the fodder availability in the area.